Kegiatan Pengabdian Masyarakat dengan Pemeriksaan Komposisi Tubuh pada Kelompok Usia Remaja di SMA Kalam Kudus 2 - Ruslim, Daniel; Santoso, Alexander Halim; Soeltanong, Dianova; Soebrata, Linginda; Rayhan , Naufal; Setia, Nicholas; Destra, Edwin (Jurnal Pengabdian Bidang Kesehatan, 2024)
Body composition is the ratio of fat mass to fat-free mass in the body, which is an important factor in maintaining health, especially in adolescents who are experiencing rapid growth and development. Balanced body composition in adolescence can support physical health and prevent various diseases. Imbalanced body composition has the potential to cause obesity, metabolic disorders, heart disease, and musculoskeletal problems. Educational activities and body composition examinations are carried out using the PDCA (Plan-Do-Check-Act) approach, involving counseling on healthy lifestyles and body composition examinations. This program has succeeded in increasing adolescents' understanding of the importance of maintaining body composition balance and adopting healthy habits. Health education and routine body composition monitoring provide benefits in preventive efforts to prevent future health risks. Continuous body composition examinations and education are important steps in efforts to control health among adolescents.